HORMONAL AND BIO-CHEMICAL PROFILE AND EARLY PREGNANCY DIAGNOSIS BY ULTRASONOGRAPHY IN THOROUGHBRED MARES - RABARI, M L; SHAH, R G; TANK, P H; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
This work was carried out on 45 Thoroughbred mares of private stud farm of North Gujarat during breedingseason. The mares bred naturally were subjected to per rectal examination and ultrasonography for the pregnancystatus and were divided into pregnant (n=35) and non-pregnant (n=10) groups. The pregnant mares were furtherdistributed in three Groups as per the gestation days, viz., i) Group-I: mares between 0-35 days of gestation(n=12), ii) Group-II: mares between 36-75 days of gestation (n=12), iii) Group-Ill: mares between 76-150 days ofgestation (n=11 ). The mean plasma progesterone level (ng/ml) of pregnant mares was significantly (P11 ng/ml).
Keywords: Thoroughbred mare; early pregnancy diagnosis; hormonal profile; biochemical profile; ultrasonography